Konseling Islam Berbasis Tarekat Qodiriyah-Naqsyabandiyah: Studi Dinamika di Pesantren Suryalaya dan Implikasinya terhadap Pengembangan Konseling Islam - Fahrudi, Emi; Irfan; Mundofi, Ahmad Asron; Urokhim, Auliya; Yusuf, Moh. Asror (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2025)
This research examines the therapeutic potential of the Qodiriyah-Naqsyabandiyah Tariqa (TQN) spiritual tradition as a solution to the need for a holistic and relevant Islamic counseling model. Focusing on Pesantren Suryalaya as a case study, the study aims to analyze the dynamics of TQN's spiritual guidance, identify its therapeutic elements, and formulate a tariqa-based counseling model. Using a qualitative case study approach, data were gathered through participant observation, in-depth interviews, and documentation study at pesantren suralaya. ata  analysis was  carried  out  using  the  Miles  and  Huberman  model,  which includes    data    reduction,data    presentation,    and    drawing conclusions. The findings reveal an effective integrative counseling model that blends Sufi practices such as dhikr, riyadhah, and reflective dialogue with core Islamic values like sabr (patience), tawakkul (reliance on God), and ridha (sincere acceptance). This model is proven to address psycho-spiritual issues and strengthen the character of students through a holistic collaboration among counselors, caregivers, and religious leaders (kiai). Although challenges exist, such as the potential for reducing the tariqa's meaning and low spiritual literacy among counselors, the study emphasizes the urgency of overcoming them through Sufi-based counselor training and the development of hybrid digital platforms. Overall, these findings affirm the relevance of the tariqa tradition in shaping a holistic, value-based, and contextual Islamic counseling practice amidst modern challenges.